1978
DOI: 10.1172/jci109023
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Bicarbonate Exit Step in Urinary Acidification by a Disulfonic Stilbene

Abstract: A B S T R A C T Acidification of the luminal solution by the isolated turtle bladder involves H+ secretion by a pump at the luminal membrane. The OH-dissociated in this process reacts with CO2 and forms HCO-which moves passively out of the cell across the serosal cell membrane. In the present study, this exit step for HCO3 was inhibited by serosal addition of the disulfonic stilbene, SITS, an agent which is thought to bind to a transport protein at the serosal cell membrane. 90 min after serosal addition of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…Similar conclusions have been suggested by a recent study of in vitro, isolated, perfused, rabbit proximal convoluted tubules (57). The turtle bladder also has a conductive pathway for bicarbonate diffusion across the serosal membrane (32,33), and SITS inhibits anion transport on that side of either tissue (32,33,36). We cannot rule out an effect on the pertibular membrane in our studies because large concentrations of the drugs were used, and some fraction may have been reabsorbed and affected peritubular anion transport.…”
Section: Neutral Sodium Chloride Transportsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar conclusions have been suggested by a recent study of in vitro, isolated, perfused, rabbit proximal convoluted tubules (57). The turtle bladder also has a conductive pathway for bicarbonate diffusion across the serosal membrane (32,33), and SITS inhibits anion transport on that side of either tissue (32,33,36). We cannot rule out an effect on the pertibular membrane in our studies because large concentrations of the drugs were used, and some fraction may have been reabsorbed and affected peritubular anion transport.…”
Section: Neutral Sodium Chloride Transportsupporting
confidence: 76%
“…The effects of furosemide upon electrogenic sodium reabsorption were examined in the last series of (27) found that 1 mM furosemide reduced volume reabsorption by 50% in the perfused rat ileum. Similar doses of furosemide (1)(2)(3)(4)(5) mM) also inhibit chloride transport across the erythrocyte membrane (28,29), primarily by inhibiting an anion exchange and transport in many physiological systems (30)(31)(32)(33)(34)(35)(36) …”
Section: Methodsmentioning
confidence: 99%
“…II]. Obviously, the DMO method simply enables the qual itative indication of the changes in mean cell pH in the tissue but falls short of giving a precise estimation of cytosolic pH in a particular group of cells when a heterogeneous tissue is evaluated: the various cell types that compose the turtle urinary bladder have different pH values as demonstrated by the relatively alkaline cell pH recently shown to be present in the CA-rich cells [10].…”
Section: Role O F Cell Phmentioning
confidence: 99%
“…Gluck et al [16] have shown that a low ambient pH docs not stimulate the H ' ATPase isolated from the fresh-water turtle bladder. Depres sion by carbonic anhydrase (CA) inhibitors of both H ' and HCO3 secretion in tight urinary epithelia results in variable changes in intra cellular acidity, often in the opposite direc tion to those expected if cytosolic pH were a major regulator of JH ' and JHCOj [30], Although the effects of sulfones on JH ' have been attributed to their effect on cell pH [10], the almost complete inhibition of mucosal acidification by a disulfonic stilbene is ac companied by only a minimal change in the [Ht ] in the cytosol. Moreover, the pH gra dient necessary to nullify H+ secretion is the same regardless of the magnitude of JH + and of the CO2 level, indicating that substantial changes in cell pH cannot be invoked as the cause of changes in mucosal acidification in response to CO2 [3], In addition, the notion that intracellular acidosis stimulates JH ' needs to be reconciled with biochemical evi dence that the maximal activity of a number of H+ ATPase of membrane origin is at alkal ine pH [21],…”
Section: Introductionmentioning
confidence: 99%
“…SITS (4-isothiocyano-4'-acetamido-2,2'-disulfonic stilbene) has been shown to inhibit urinary acidification [2,3]. This inhibition is due to interference with the efflux of bicarbonate across the serosal membrane [2]. We therefore examined the effects of this agent on the exchange flows of chloride and bicarbonate.…”
mentioning
confidence: 99%